Glenoid loosening and migration in reverse shoulder arthroplasty. (April 2019) - Lädermann, A.; Schwitzguebel, A. J.; Edwards, T. B.; Godeneche, A.; Favard, L.; Walch, G.; Sirveaux, F.; Boileau, P.; Gerber, C.
Abstract : Aims: The aim of this study was to report the outcomes of different treatment options for glenoid loosening following reverse shoulder arthroplasty (RSA) at a minimum follow-up of two years. Patients and Methods: We retrospectively studied the records of 79 patients (19 men, 60 women; 84 shoulders) aged 70.4 years (21 to 87) treated for aseptic loosening of the glenosphere following RSA. Clinical evaluation included pre- and post-treatment active anterior elevation (AAE), external rotation, and Constant score. Results: From the original cohort, 29 shoulders (35%) were treated conservatively, 27 shoulders (32%) were revised by revision of the glenosphere, and 28 shoulders (33%) were converted to hemiarthroplasty. At last follow-up, conservative treatment and glenoid revision significantly improved AAE, total Constant score, and pain, while hemiarthroplasty did not improve range of movement or clinical scores. Multivariable analysis confirmed that conservative treatment and glenoid revision achieved similar improvements in pain (glenoid revision vs conservative, beta 0.44; p = 0.834) but that outcomes were significantly worse following hemiarthroplasty (beta -5.00; p = 0.029). Conclusion: When possible, glenoid loosening after RSA should first be treated conservatively, then by glenosphere revision if necessary, and last by salvage hemiarthroplasty Cite this article: Bone Joint J 2019;101-B:461–469.